Determinants of the successful single stock futures market in Thailand - Woradee Jongadsayakul (Investment Management & Financial Innovations, 2022)
Thailand’s Single Stock Futures market has grown recently over the last ten years, evidenced by its 8th place in top 10 exchanges in the world by number of single stock futures traded in 2021. Since the main goal of any futures exchange is to list a successful contact, it is important to demonstrate the determinants of the success of Single Stock Futures. This study uses the sample consisting of 89 companies, on which stocks are underlying for Single Stock Futures in the period between January 2017 and December 2021, and finds that the best fitting method in modelling determinants of the success of Single Stock Futures is the fixed effects model. As expected, the results confirm the existence of a positive relationship between characteristics of underlying stock, including size, volatility, and liquidity, and the successful futures contract. Furthermore, the findings show the negative effects of the first year of contract trading and the tightened daily price limit of Single Stock Futures in response to the COVID-19 pandemic situation on contract success. AcknowledgmentThe author is grateful to the Department of Economics, Faculty of Economics, Kasetsart University for financial support to conduct this research.